Os argumentos de licenciandos em Biologia sobre o uso do conceito de raça para seres humanos em uma sequência de ensino investigativa - Rezende, Ayslan Sobral (2019)
The concept of race has historically been used in different ways in different areas of knowledge, extending even to the human species, in order to characterize individuals or social groups. Considering the current paradigm of biology, the traditional classificatory concept of race as a delimiter of significant differences between humans is invalid. However, despite its inconsistency from a biological point of view, the idea of race continues to be used as a demarcation of differences between people, especially in relation to the identity of specific groups in society. Considering the importance of problematizing the ideas related to this concept, its appropriations and its unfolding in different fields of knowledge and social spheres, we seek in this research to characterize the structure and the quality of the arguments elaborated by a group of graduates of the course of Biology of the UFS on the theme "Human Race", considering the dialectical and rhetorical aspects involved, in order to highlight the different appropriations of this concept in the context of the application of SEI. With this objective, a Sequence of Investigative Teaching (SEI) was applied to students of a pedagogical discipline of such course. The SEI was structured with inspiration in the model proposed by Pedaste (2015) and has as central question: "Is the use of the concept of race for human beings pertinent?" The data were collected through a questionnaire containing the central question of SEI. For the analysis, we use the model proposed by Osborne, Erduran and Simon (2004), which corresponds to an adaptation of Toulmin's model (1958). The results indicate that the majority of lienciandos considers the use of the term race for humans to be pertinent, but it places restrictions on such use, since it is associated with prejudiced and discriminatory ideas. The justifications, for the most part, have contributions in conceptions that represent superficial appropriations of the scientific discourse, both of the social sciences, as well as of the biological ones. It shows little deepening of the discourse of Biology, of the contributions of Genetics to justify the points of view presented. However, it can be inferred that some of the graduates consider the biological reference to the concept of race fragile, especially because they emphasize its relevance in the dimension of social construction and contribution to the identity of the people. From the point of view of the structure of the arguments, 7 groups were found, and the most complex arguments presented the following elements: Data (D), Conclusion (C), Conditions for Completion (CPC), Knowledge Base (CB) and Refutator ( R). The simplest arguments consisted only of theoretical data (D) and conclusion (C). We also found texts that did not constitute arguments, because they did not provide justifications for the proposed conclusions or because they did not present a definite conclusion.